The Impact of Cash and Food Transfers Linked to Preschool Enrollment on Child Nutrition and Cognitive Outcomes - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
School feeding programs provide students meals conditional on school attendance, which can have impacts on school participation, cognition and learning, and nutritional outcomes. Although the literature on impacts of school feeding programs is substantial, high quality studies with evaluation designs that provide causal impact estimates are relatively few. Thus program impacts on educational, cognitive and nutritional outcomes are not well-understood, particularly in a field setting. Nutritional impacts in particular are questionable, which may be a result program design. Most studies provide only small transfers to children and examine average macro-nutrient effects of the transfer on the treated children, thus it is not surprising that detection of nutritional gains has been minimal.This study is a cluster-randomized evaluation of a school feeding program administered by the World Food Programme in the Northern Ugandan Districts of Lira and Pader. The program provides substantially larger food rations than most programs (representing 1/3 of children's daily caloric needs and 99% of iron intake requirements).The key research objectives are:Impact on the treated: Assess the effectiveness of the program at improving nutritional status, education and cognitive and learning outcomes for school-age children, with particular attention to the anemia status of older school-age girls .Impact on untreated but nutritionally vulnerable sub-groups: Assess the effectiveness of the program at reducing anemia prevalence in mothers and younger siblings.Optimal program design: Assess the differential impacts of a program in which children are fed at school compared with one in which they are given dry rations to bring home.